Peran Konseling Komunitas dalam Meningkatkan Self-Esteem Penyandang Disabilitas - Wijaya, Anindya Kinasih Putri; Arifin, Alvenia Clarista; Imannudin, Wahyu; Rahman, Waly Yafi; M, Muslikah; Mahfud, Ashari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Persons with disabilities in Indonesia face various physical, mental, and social challenges that significantly affect their self-esteem. This study aims to explore the role of community counseling in enhancing the self-esteem of individuals with disabilities. Employing a literature review methodology, this research analyzed relevant theories and empirical findings. The results indicate that community counseling, based on social support and individual empowerment, effectively enhances self-esteem by providing an inclusive, supportive, and empowering environment. Additionally, community counseling helps individuals overcome social stigma, strengthen their support networks, and build self-confidence. The conclusion emphasizes the importance of integrating culturally sensitive and technology-driven approaches to improve service accessibility. The study's implications include recommendations for developing more inclusive and adaptive community counseling programs to address the unique needs of persons with disabilities in Indonesia.